2016
DOI: 10.1097/ogx.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use Among Women During Pregnancy and Childbearing Years

Abstract: Objectives: Little is known regarding complementary and alternative medicine (CAM) use during pregnancy and the preconception period. Since half of all pregnancies in the United States are unintended, understanding the patterns of CAM use among women of childbearing age has implications for fetal and maternal health. Methods: Descriptive statistics were generated from the 2012 National Health Interview Study (NHIS) to estimate weighted prevalence and patterns of CAM use by women of childbearing age. Comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…18 These mind-body and body based manipulative practices are readily available to the general public and appear to be the most common complementary and alternative medicine modalities used in pregnancy. 19 Several Cochrane reviews support the use of acupuncture, acupressure, yoga, and relaxation techniques to reduce labor pain and increasing satisfaction with pain relief. 5,6…”
Section: Discussionmentioning
confidence: 99%
“…18 These mind-body and body based manipulative practices are readily available to the general public and appear to be the most common complementary and alternative medicine modalities used in pregnancy. 19 Several Cochrane reviews support the use of acupuncture, acupressure, yoga, and relaxation techniques to reduce labor pain and increasing satisfaction with pain relief. 5,6…”
Section: Discussionmentioning
confidence: 99%
“…2227 In the United States, an estimated 13% of pregnant women practice yoga. 28 However, rigorous prospective feasibility, safety, and efficacy data are limited. In the nonpregnant patient population, U.S. studies suggest that yoga is an effective intervention for back pain and overall well-being.…”
Section: Introductionmentioning
confidence: 99%
“…This study begins to address the paucity of literature regarding the safety of herbal products that are used during lactation. Despite little data on the subject, it is estimated that between 22 and 45% of women in the United States use herbal products, and this extends to women during pregnancy and lactation (Budzynska et al, 2012;Holden, Gardiner, Birdee, Davis, & Yeh, 2015), with higher rates of use reported in Australia (Sim, Sherriff, Hattingh, Parsons, & Tee, 2013) and Italy (Aleandri et al, 2014). Thus, there is great need for well-designed studies to measure safety and efficacy of various herbal products.…”
Section: Discussionmentioning
confidence: 99%